Penerapan Pola Hidup Sehat untuk Mengurangi Penyebaran Covid-19 di kecamatan Kedopok kota Probolinggo - Renny Augustina (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas Panca Marga Probolinggo, 2021)
The spread of the Covid-19 virus is increasing faster through droplets of saliva or coming out of the nose when an infected person coughs or sneezes. However, there is still very little understanding and awareness of the public to comply with health protocols when doing activities outside the home. Therefore, it is necessary to carry out efforts to increase understanding of Covid-19 and the importance of increasing compliance with the implementation of health protocols to overcome Covid-19. Based on these problems, the authors carry out community service activities in the form of UPM Thematic Real Work Lecture (KKN) in the Covid-19 Era. Activities carried out by means of countermeasures through programs that we have been prepared in order to prevent the spread of Covid-19 in the Kedopok sub-district, Probolinggo city. In this KKN program, programs such as the distribution of handsanitizers and masks, planting trees and toga, joint exercise and making herbal medicine and education on health protocols in several villages in the Kedopok sub-district, Probolinggo city are carried out. As a result of the implementation of this Community Service Program, 25 masks, 90 bottles of handsanitizer, 2 educational banners, 50 educational stickers and 6 liters of disinfectant liquid have been made and distributed to people in the Kedopok sub-district, Probolinggo. Keywords: covid 19, healthy life, KKN UPM